OLGA: Innovative Local Wisdom-Based Marine Ecology Learning Media for Fifth-Grade Students - Laily, Yulia Nisfiatul; Ramadhani, Amalia Ulfa; Dimyati, Maftuh Fauji; Wijayanti, Arfilia (Universitas Negeri Semarang, 2024)
This study introduces OLGA (Ocean Lomban Game), an innovative learning media integrating local wisdom to enhance marine ecology education for fifth-grade elementary students. Given the serious threats to global marine resources from human activities and climate change, early aquatic ecology and conservation education is crucial. OLGA incorporates the traditional Lomban Kupatan ritual from Tayu, Pati, emphasizing ecological balance and cultural heritage. Using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the research involved evaluating current curriculum needs, designing a storyboard, developing the game with MIT App Inventor and animation videos, and implementing it in a classroom setting. Pre-tests and post-tests were conducted to measure effectiveness. The results indicated that OLGA significantly improved students' interest and performance in learning marine ecology. Validation by experts confirmed the media's suitability and effectiveness. Teacher and student feedback highlighted its practicality and ease of use, making OLGA a promising educational tool. The study concludes that OLGA effectively combines science education with local cultural elements to foster ecological awareness among students.